Success in the treatment of the Skeletal Cl III Cases - Mirzen Arat; Ayşegül Köklü; Canan Merzeci; Meliha Rübendüz (Galenos Yayinevi, 1988)
Successfull results are obtained by the orthopedic treatment of the skeletal Cl III cases in the early growth period. However, one cannot be sure about the stability of these results unless necessary precautions are taken till the end of the mandibular growth. In the later periods of growth; if the discrepency between the maxillary and the mandibulary arches can be shadowed only by orthodontic treatment, optimum results can be obtained.